Agenda Riset Prioritas Tentang Komersialisasi Ruang Terbuka Hijau Publik dan Kaitannya dengan Pandemi Covid-19 - Agustina, Sylvia; Safriana, Desi; Ardesir, Jannata; Nasron, Rifani (Jurnal Pembangunan Wilayah dan Kota, 2021)
The Spatial Planning Law of the Republic of Indonesia requires cities to provide a minimum of 30% land for green open space (RTH). In the midst of meeting this target, the commercial use of public green open space is growing. The situation can potentially reduce the effective area used for the public and affect the quantity of space, as well as the quality of citizen interaction with green open space. This study aims to identify the type and level of public green open space commercialization in Banda Aceh, identify research themes related to green open space commercialization, and formulate a priority list for further study taking into account the conditions of the Covid-19 pandemic. The research was conducted through focus group discussions, field observations, interviews and opinion polls. Preliminary research results in Banda Aceh indicate that commercial activities have the potential to transform public green open space into quasi-public. The presence of multi actors in the management of commercial activities in RTH can be a synergy, but it can also be a contest. The impact of the decrease in visits and the intensity of commercial activities occurred in the early days of the pandemic, but has increased again so that special handling is needed. The focus of research related to the use of green open space as an alternative space for interaction, especially during the pandemic, needs to be formulated with an interdisciplinary approach. The identified priority research agendas are those of applied research characteristics, namely the complete mapping of green open space that is affected by commercial activities and the application of micro zoning to control space use in green open space, including to mitigate the potential spread of the covid-19 outbreak.